2017
DOI: 10.1038/s41598-017-00790-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvia fruticosa Induces Vasorelaxation In Rat Isolated Thoracic Aorta: Role of the PI3K/Akt/eNOS/NO/cGMP Signaling Pathway

Abstract: Salvia fruticosa (SF) Mill. is traditionally used for its antihypertensive actions. However, little is known about its pharmacologic and molecular mechanisms of action. Here we determined the effects of an ethanolic extract of SF leaves on rings of isolated thoracic aorta from Sprague-Dawley rats. Our results show that SF extract increased nitric oxide production and relaxed endothelium-intact rings in a dose-dependent (0.3 µg/ml–1 mg/ml) manner, and the maximum arterial relaxation (Rmax) was significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 78 publications
8
32
0
Order By: Relevance
“…The buffer was continuously aerated with 5% CO 2 in oxygen to maintain the pH of KHB at 7.4. The rings were equilibrated for an hour, subjected to a stepwise increase in tension of 0.5 g every 15 min till a final resting tension of 2 g was attained, subsequent to each incremental rise in tension the rings were washed with fresh buffer ( Anwar et al, 2017 ). Tension changes in aortic ring responses were recorded by a computerized PowerLab data acquisition system (AD Instruments, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The buffer was continuously aerated with 5% CO 2 in oxygen to maintain the pH of KHB at 7.4. The rings were equilibrated for an hour, subjected to a stepwise increase in tension of 0.5 g every 15 min till a final resting tension of 2 g was attained, subsequent to each incremental rise in tension the rings were washed with fresh buffer ( Anwar et al, 2017 ). Tension changes in aortic ring responses were recorded by a computerized PowerLab data acquisition system (AD Instruments, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…To decipher the signaling routes, each aortic ring was contracted with a suboptimal value of 3 μM NE, on attaining a plateau (approximately 3 min), cumulative dose response curve (CDRC) to sumac was constructed in the absence or presence of various pharmacological inhibitors ( Anwar et al, 2013 , 2017 ): L -NAME (100 μM), ODQ (10 μM), indomethacin (10 μM), glibenclamide (10 μM), TEA (100 μM), triciribine (10 μM), wortmannin (100 nM), LY294002 (10 μM), SQ22536 (100 μM), or a vehicle control. In addition to the above set of experimental data, Rhus coriaria extract (RCE)-induced arterial relaxation was determined in endothelium-denuded segments (gently rubbing in a to and from movement with a roughened piece of stainless-steel wire, covered tightly in cotton wool, along the intimae of aortic ring-generating less than 15% relaxation with acetylcholine).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Stimulation of Akt enhances the activity of eNOS by phosphorylating serine at 1,177 and triggers the release of NO. 44 To test our hypothesis, we chose a 30 μM concentration for all subsequent experiments in accordance with the dose-dependent dilation of FMN. FMN augmented cellular NO production via eNOS phosphorylation, which is evident from the suppression of this effect by l -NAME.…”
Section: Discussionmentioning
confidence: 99%
“…radix is a herbal formula suppress the expression of ICAM-1 and VCAM-1 and production of MCP-1 in TNF-a stimulated human umbilical vein endothelial cells (Koon et al, 2011). Sage also has antihypertensive activity as it was shown that sage extract increased nitric oxide production and relaxed endothelium-intact rings in experiments on isolated thoracic aorta from rats (Anwar et al, 2017).…”
Section: Possible Anti-atherosclerotic Mechanisms Of Medicinal Plantsmentioning
confidence: 99%